The Perception of Value in the Luxury Real Estate Market: An Analysis from the Customer’s Perspective - Chacur, Lucas; de Oliveira Dias, Murillo (Archives of Business Research, 2025)
Customer experience generally encompasses the views and feelings emerging from contacts with a supplier's people, channels, and products, for example. Through qualitative in-depth interviews with N=25 sector experts, we explored the elements that impact the customer experience in the Brazilian luxury real estate market from the customers' perspective. Due to the discrepancy between the subject's literature study and the natural world scenario, the comprehensive content analysis revealed that luxury real estate requires more research. Therefore, the present study concludes with a discussion and management recommendations.